2013
DOI: 10.4103/2229-5178.120662
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory vitiligo versus hypopigmented mycosis fungoides in a 58-year-old Indian female

Abstract: Vitiligo, particularly the rarer inflammatory variant, may be difficult to distinguish from hypopigmented mycosis fungoides (MF) clinically. Complicating the distinction is that when biopsies are taken from the periphery of early vitiliginous lesions or from lesions with an inflammatory border (inflammatory vitiligo), a dermal lymphocytic infiltrate, exocytosis, interface dermatitis, and mild spongiosis may be seen, all resembling the findings seen in hypopigmented MF. We present a case demonstrating the diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The presence of CD8-positive lymphocytes tagging the dermoepidermal junction as well as ringing melanocytes is in line with recent work in murine models implicating CD8-positive cells as the effectors of melanocyte death [7]. Other reports in the literature describe the inflammatory border of IVRB as presenting with band-like infiltration of lymphocytes in the upper dermis, including CD4-positive and CD8-positive cells (see table 1 for selected examples) [2,8,11,12]. Le Poole et al [6] suggest that HLA-DR expression along stretches of basal and suprabasal keratinocytes may contribute to local T cell reactivity.…”
Section: Discussionsupporting
confidence: 64%
“…The presence of CD8-positive lymphocytes tagging the dermoepidermal junction as well as ringing melanocytes is in line with recent work in murine models implicating CD8-positive cells as the effectors of melanocyte death [7]. Other reports in the literature describe the inflammatory border of IVRB as presenting with band-like infiltration of lymphocytes in the upper dermis, including CD4-positive and CD8-positive cells (see table 1 for selected examples) [2,8,11,12]. Le Poole et al [6] suggest that HLA-DR expression along stretches of basal and suprabasal keratinocytes may contribute to local T cell reactivity.…”
Section: Discussionsupporting
confidence: 64%
“…Due to its inflammatory aspect, we recorded whether other concomitant diseases were reported (Table ). Autoimmunity was reported in 11 cases of these 25 cases . Inflammatory vitiligo needs to be differentiated from other dermatoses (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These inflammatory symptoms are described as ‘rare’ cases. Raised borders have been reported to affects less than 5% of all vitiligo cases, while another study reported erythema, scaling and/or hyperpigmentation in 13% . Due to its inflammatory aspect, we recorded whether other concomitant diseases were reported (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis was given to each case based on constellation of clinical and histopathological findings and according to criteria described in the literature. 3,4,[7][8][9][10][11][12][13][14] Data were coded and entered using Statistical Package for Special Science (SPSS) software computer program version 15. Data were described as mean 6 SD for quantitative (numerical) variables and as frequency and percentage for qualitative (categorical) variables.…”
Section: Methodsmentioning
confidence: 99%